Development of Portable Air Conditioning System Using Peltier and Seebeck Effect - Shafiei, Nuraini; Harun, Mohamad Haniff; Mohd Annuar, Khalil Azha; Mohd Firdaus, Mohd Ab Halim; Mohd Shahrieel, Mohd Aras; Arman Hadi, Azahar (Penerbit Universiti, UTeM, 2016)
The society bustle factor in this day and age, most people want to find equipment that is often used in everyday life in a small and light weight design. The purpose of this project is to develop portable air conditioning system without using any gas. The system used thermoelectric heat pump as main device for producing cool air known as Peltier Effect. The generating system theoretically can recycle the heat loss to produce additional electricity for other usage. The efficacy of this system tested using two types of experimental using Peltier and Seebeck Effect. Both experimental are conducted using 3 specific volumes; 1) 1000cm3; 2) 4000cm3; and 3) 9000cm3. As a result, temperature for heating and cooling systems achieve around 16 – 40 degree Celcius (oC) while the voltage generated around 12V in 30 minutes.